DOES EARNINGS QUALITY MODERATE THE PREDICTIVE CONTENT OF NONOPERATING INCOME? - Sugiri, Slamet (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
The objective of this study is to empirically examine a hypothesis that earnings quality enhances the ability of nonoperating income to predict future operating cash flow. The magnitude of income smoothing index, measured by Eckelâs (1981) index formula, is used to capture a firmâs quality level of earnings. Higher index is assumed to represent higher level of earnings quality. A linear regression model is developed to test the hypothesis. The model parameters are estimated based on sixty-two manufacturing firms listed in the Jakarta Stock Exchange (JSX) up to the end of 1997. This study finds empirical evidence that supports the proposed hypothesis. That is, earnings quality enhances the predictive content of nonoperating income.